Sehat Bersama, Kolestrol Terjaga dengan Senam Sehat dan Pemeriksaan Kolestrol Gratis pada Kelompok Masyarakat di Desa Karawana, Kecamatan Dolo, Kabupaten Sigi. - Riskayanti Riskayanti; Hermin Lastri Gintoe; Slamet Ifandi; Enggar Enggar (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2024)
Health is an important factor that influences the quality of life of the community. This study aims to increase awareness of the people of Karawana Village, Dolo District, Sigi Regency, about the importance of maintaining cholesterol levels through regular physical activity. The methods used include counseling, healthy exercise, and cholesterol checks using a cholesterol meter. This activity was attended by 8 participants aged over 40 years. The results showed that 2 participants had total cholesterol levels above 239 mg/dL, which indicates a high risk of cardiovascular disease. The education provided succeeded in increasing public understanding of the importance of a healthy lifestyle and regular health checks. The conclusion of this activity is the need for follow-up in the form of health counseling and ongoing education programs to maintain public health related to cholesterol.